(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Quality by Design (QbD) is well established in the pharmaceutical industry for pharmaceutical development and manufacturing processes. The knowledge obtained during development may support the establishment of a design space and determines suitable process controls. This same QbD principle has been applied to the development of analytical methods and is termed “Analytical Quality by Design” (AQbD). Analogous to process QbD, the outcome of AQbD is well understood, fit for purpose, and robust method that consistently delivers the intended performance throughout its life cycle. The present work is aimed to develop an AQbD approach to analytical method development and validation based of Tadalafil and its impurities by the NP-HPLC method. The other objective of this work is to establish an in-depth understanding of the method and build in the quality during the method development to ensure optimum method performance over the lifetime of the product.